«Խոսելու ժամանակը եկել է». Մեծ եղեռնը եւ հայկական հարցը գերմանա–հայկական ընկերության հետպատերազմյան հրապարակախոսության մեջ - Հրանուշ Սահակյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
После Первой мировой войны Иоганнес Лепсиус продолжал заниматься вопросом осуждения и наказания за преступления, совершенных против армянского народа. В мае 1919 года вышел в свет сборник документов «Германия и Армения 1914–1918 гг.», состоявший из 444 сообщений. After World War I, Johannes Lepsius continued to serve the cause of condemning crimes against the Armenian nation and of claiming fair punishment for those crimes. In May 1919 a collection of documents prepared by Lepsius and entitled “Germany and Armenia in 1914-1918” that consisted of 444 reports was published.
Keywords: History